Emerging Role of Electronic Human Resources Management Functions in Jordan - A Critical Review - Hadeel Mansour; Ishaq Ibrahim; Bha-Aldan Mundher Oraibi; Odai Enaizan (Journal of Advance and Future Research, 2024)
Non-Indexed Publication